The Effectiveness of the Project-Based Learning Model to Enhance High School Students’ Problem-Solving Skills in the City of Mataram, West Nusa Tenggara - Sri Suci Lestari; Widuri Permata Anggarbini Rayis; Marjan Marjan (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
21st-century physics learning requires problem-solving skills, but school practices often remain teacher-centered and formula-oriented. This study aims to analyze the effect of implementing a project-based learning model on 11th-grade students’ problem-solving skills in linear motion at SMA Negeri 2 Mataram. The research used a one-group pretest-posttest design with a purposively selected sample of 71 students. The results indicated strong validity (17 of 20 items were valid) and high reliability (KR-20 = 0.854). The average score went up from 63.24 on the pretest to 70.12 on the posttest. Normality testing confirmed that the data were normally distributed, and the paired sample t-test showed a significant difference (t-value of 5.527 exceeded the t-table value of 2.000). These findings confirm that project-based learning is efficacious in improving students’ problem-solving skills. The PjBL model is effective in developing these skills and can serve as an innovative learning strategy to enhance physics learning in secondary schools.